Impact of COVID-19 on the Speech and Language Therapy Profession and Their Patients - Chadd, Katie; Moyse, Kathryn; Enderby, Pam (Frontiers in Neurology, 2021)
Introduction: The UK's response to the COVID-19 pandemic presented multiple challenges to healthcare services including the suspension of non-urgent care. The impact on neurorehabilitation professions, including speech and language therapy (SLT), has been substantial. Objectives: To review the changes to SLT services triggered by the COVID-19 pandemic with respect to referral rates, service delivery and outcomes, as well as examining the contribution of SLTs to the neurorehabilitation of COVID-19 patients. Methods: Two surveys were distributed to Royal College of Speech and Language Therapists (RCSLT) members exploring experiences of service provision at 6 weeks and 22 weeks after the pandemic was declared in the UK. Responses to closed-ended questions, including questions regarding referral numbers were analyzed descriptively and compared at the two time-points. A database comprising routine clinical data from SLT services across the UK was used to compare information on patients receiving services prior to and during the pandemic. Data on COVID-19 patients was extracted, and findings are provided descriptively. Results: Referrals to SLT services during the acute COVID-19 period in the UK were substantially less than in the same period in 2019. A number of service changes were common including adopting more flexible approaches to provision (such as tele-therapy) and being unable to provide services to some patients. Database analysis suggests fewer patients have accessed SLT since the pandemic began, including a reduction in neurorehabilitation patients. For those who received SLT, the outcomes did not change. SLTs supported a range of needs of COVID-19 patients. Treatment outcomes for COVID-19 patients with dysphagia were positive. Discussion: The pandemic has affected neurorehabilitation and SLT services broadly: referral patterns are different, usual care has been disrupted and interventions have been modified affecting the impact on patient outcomes both positively and negatively. Some patients with COVID-19 require and benefit from SLT intervention.